Pretend play of children in the U.P. Child Development Center - De Castro, Nica Mae L.; De los Angeles, Paulina Enrica Y. (College of Home Economics, University of the Philippines Diliman, 2019)
Currently, there are very limited studies on the play, specifically pretend play of Filipino children. Given that play is a culturally mediated activity, this study focused on describing the pretend play of four-year-old Filipino children in the U.P. Child Development Center. This was done through a qualitative study that addresses the research gaps by looking into the elements and the context that are prevalent in the pretend play of Filipino children. . Particularly, the researchers looked into the elements or components that make up the pretend play, such as, the use of play materials, the roles and characters, and the use of language when at play. The study also looked into the context or the circumstances surrounding pretend play, such as, the themes, setting, actors involved, and participation of adults. The data was obtained through naturalistic observation of a preschool class composed of 18 four-year-old children. The children were observed during their Free Play for a total of 12 days or seven hours and 45 minutes of observation. It was found that the pretend play of the children reflected the universal dimensions of pretend play, namely, the use of play objects, presence of themes, and the involvement of roles and characters. Some elements and context that were found were similar with those of cross-cultural studies done before.